EORTC 2238 “De-Escalate”: a pragmatic trial to revisit intermittent androgen deprivation therapy in the era of new androgen receptor pathway inhibitors - Grisay, Guillaume; Turco, Fabio; Litiere, Saskia; Fournier, Béatrice; Patrikidou, Anna; Gallardo, Enrique; McDermott, Ray; Alanya, Ahu; Gillessen, Silke; Tombal, Bertrand (Frontiers in Oncology, 2024)
The landscape of treating metastatic prostate cancer has evolved with the addition of Androgen Receptor pathway inhibitor (ARPI) to Androgen Deprivation Therapy (ADT), significantly improving survival rates. However, prolonged use of these therapies introduces notable side effects, prompting a need to revisit intermittent treatment duration. The EORTC 2238 De-Escalate trial is a pragmatic trial seeking to reassess the role of intermittent therapy in patients undergoing maximal androgen blockade (MAB) for metastatic hormone naïve prostate cancer (mHNPC), i.e., the combination of ADT with an ARPI, with the aims of reducing side effects, enhancing Quality of Life (QoL) and optimizing resource usage, while maintaining oncological benefits.